Abdominal Wall Reconstruction with a Free Fibula Flap after Internal Extended Hemipelvectomy - Pedro C. Cavadas; Daniela Téllez-Palacios (Indian Journal of Plastic Surgery)
Major pelvic resections for malignant tumors are infrequent and have significant morbidity and mortality, for instance, incisional hernias are postoperative complications uncommonly reported probably because most cases are overshadowed by more serious complications. Reconstruction depends on the extent of the resection and overall prognosis of the patient. A case of a late complex hypogastric and femoral incisional hernia after extended hemipelvectomy for recurrent osteosarcoma treated with distal abdominal wall fixation into a free fibula flap is reported.